Pete the cat [compact disc]. - Stoner, Alyson, 1993-; Ferguson, Jesse Tyler; Costello, Elvis; Krall, Diana; Tunstall, KT; Mraz, Jason; Matthews, Dave, 1967-; Marsh, Django; Freund, Tom, 1968-; Tremblay, Jacob; Shaffer, Atticus, 1998-; Marsh, Jeff, 1960-; et al. (Sleeping Giant Music, 2018)
The first soundtrack from the animated series featuring songs done by Elvis Costello, Diana Krall, KT Tunstall, Don Was, Jason Mraz, and many more.